Polysensitization in Recurrent Lip Dermatitis. Issue 1 (January 2015) - Fraser, Kathleen; Pratt, Melanie
Background: In allergic contact dermatitis (ACD), polysensitization consists of positive patch test reactions to three or more unrelated allergens. Objective: The purpose of this case report is to document a 27-year-old female with recurrent lip dermatitis, polysensitization, and reactions to a number of clinically relevant exposures. Methods: Patch testing results revealed positive reactions to tixocortol-21-pivalate (3+), lanolin (3+), neomycin (3+), nickel (1+), hydroxyethyl methylacrylate (3+), bacitracin (3+), and abitol (3+). Results: The patient had seven positive reactions, meeting the criteria for polysensitization. Of known clinical relevance, the patient had applied lanolin-containing lip balms and hydrocortisone- and bacitracin-containing products to the lips, all of which she was strongly reactive to on patch testing. Conclusion: Polysensitization occurs when three or more unrelated allergens are positive on patch testing. This case highlights the importance of considering polysensitization in ACD as numerous allergens that were positive on patch testing were clinically relevant.